Genotype x environment interactions of yield of cowpea (Vigna unguiculata (L.) Walp) inbred lines in the Guinea and Sudan Savanna ecologies of Ghana - Owusu, E.Y.; Amegbor, I.K.; Mohammed, H.; Kusi, F.; Atopkle, I.; Sie, E.K.; Ishahku, M.; Zakaria, M.; Iddrisu, S.; Kendey, H.A.; Boukar, O.; Fatokun, C.; et al. (Springer, 2020)
The variable cowpea productivity across different environments demands evaluating the performance of genotypes in a breeding program prior to their release. The aim of this study was to assess yield stability of eight cowpea advanced breeding lines selected from participatory varietal selection in multilocational trials, and to identify mega-environments for cowpea production in Ghana. The genotypes were evaluated across five environments in 2016 and 2017 in randomized complete block design with three replications. The GEA-R version 4.0 software was used for genotype main effect plus genotype by environment interaction (GGE) biplot analyses. Analysis of variance (PROC GLM of SAS using a RANDOM statement with the TEST option) detected significant variations for location, year, genotype, environment, and their interactions. The results showed that the yield performances of the cowpea genotypes were highly influenced by genotype × environment interaction effects. The principal component 1 (PC1) and PC2 were significant components which accounted for 46.75% and 22.84% of GGE sum of squares, respectively. We showed for the first time, two mega-environments for cowpea production and testing in the major cowpea production agro-ecologies in Ghana. The genotypes SARI-6-2-6 and IT07K-303-1 were adapted to Damongo, Nyankpala, and Tumu, whereas SARI-2-50-80 was adapted to Yendi and Manga. The best ranking location was Damongo followed by Tumu, and Nyankpala. The high-yielding genotypes, IT86D-610, IT10K-837-1, IT07K-303-1, and SARI-2-50-80 had significant higher grain yields than the check (Bawutawuta) and were recommended for release as cultivars (or as breeding lines) to boost cowpea production in Ghana.